2012
DOI: 10.3758/s13421-012-0279-0
|View full text |Cite
|
Sign up to set email alerts
|

Divided attention selectively impairs memory for self-relevant information

Abstract: Citation: Turk, D. J., Brady-van den Bos, M., Collard, P., Gillespie-Smith, K., Conway, M.A. & Cunningham, S.J. (2013). Divided attention selectively impairs memory for self-relevant information. Memory and Cognition, 41(4), pp. 503-510. doi: 10.3758/s13421-012-0279-0 This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent AbstractInformation that is relevant to self tends to be remembered more than information relating to other peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 46 publications
5
31
0
2
Order By: Relevance
“…We observed a pattern of results which confirms that simulating another individual's object choices based on one's own preference is associated with enhanced recollection of those objects. Specifically, we found that the ability to judge which of two previously seen (hence equally familiar) visually similar objects had previously been picked was enhanced for objects belonging to self vs. others, replicating and extending prior work using the ownership paradigm (Cunningham et al, 2008;Cunningham, van den Bos, & Turk, 2011;Serbun, Shih and Gutchess, 2010;. Critically, we also found that recollection of picked objects was significantly higher for objects belonging to the similar vs. dissimilar other.…”
Section: Discussionsupporting
confidence: 86%
“…We observed a pattern of results which confirms that simulating another individual's object choices based on one's own preference is associated with enhanced recollection of those objects. Specifically, we found that the ability to judge which of two previously seen (hence equally familiar) visually similar objects had previously been picked was enhanced for objects belonging to self vs. others, replicating and extending prior work using the ownership paradigm (Cunningham et al, 2008;Cunningham, van den Bos, & Turk, 2011;Serbun, Shih and Gutchess, 2010;. Critically, we also found that recollection of picked objects was significantly higher for objects belonging to the similar vs. dissimilar other.…”
Section: Discussionsupporting
confidence: 86%
“…35,36 However, not all the evidence indicates that selfstimuli are processed independently of attention. Turk et al 37 reported that divided attention abolished the self-advantage effect in memory, though participants remembered more items after self-ownership judgments compared with otherownership judgments when full attention was allocated. In this case, divided attention may disrupt elaborative encoding to self-referential items, 16,38 reducing the self-advantage.…”
Section: Self-biases In Attentionmentioning
confidence: 99%
“…Indeed, it is proposed that all information related to the self, is 'special' and demands preferential processing (Bargh 1982;Turk, et al, 2011;Turk, et al, 2013).…”
Section: Introductionmentioning
confidence: 99%